Effect Aqueous Extract of (Cyperus rotundus) tuber on Histological Structure of Testes in Alloxan-Induced Diabetic Male Albino Rats - Zahraa Kareem Al-Mayali (Journal of Global Pharma Technology, 2019)
Histological structure of testes in alloxan-induced diabetic rats was investigated after daily oral administration of (Cyperus rotundus) tuber aqueous extract for one month. Therty were divided into 5experimental groups, each group contain 6 adultmale albino rats weighing 150-200 g. Testes samples were obtained and processed for microscopic evaluation after staining the prepared sections with both Heamatoxylin and Eosin. There was a found severe histopatholoigical changes belong to rats injected with alloxan showing seminiferous tubules completely destroyed and nucleus going out from the testis, also presence many bleeding area, absence the connective tissue and leydig cell while showed No histological changes were found in the examined organs belong to rats treated with Extract of Cyperus rotundus.Keyword: Diabetes mellitus, Testis, male reproductive system, MSD, Cyperus rotundus, Glimepiride.